Filmin-c mutations in arrhythmogenic cardiomyopathy: a peculiar association with left dominat variant and high risk of sudden death. (25th November 2020) - Bariani, R; Celeghin, R; Bueno Marinas, M; Cason, M; Cipiriani, A; Rigato, I; Pilichou, K; Basso, C; Perazzolo Marra, M; Bauce, B
Abstract: Introduction: Arrhythmogenic cardiomyopathy (AC) is characterized by myocyte necrosis and progressive fibro-fatty substitution. Recently, truncated mutations on Filamin C gene have been correlated with AC and a peculiar phenotype characterized by a prominent left ventricular fibrosis and high risk of sudden death. Purpose: To evaluate clinical and instrumental features of subjects affected by AC in whom genetic study identified presence of truncating and missense mutations on FLNC gene. Materials and methods: A population of 192 probands affected by AC according to 2010 Task Force Criteria or McKenna's proposed criteria for left dominant AC were evaluated for FLNC variants. In positive probands and families anamnestic and clinical data (ECG, echocardiographic and cardiac magnetic resonance (CMR), twenty-four-hours ECG monitoring) were evaluated. Results: A total of 19 subjects (9 probands and 10 family members) were identified as carrier of nine different FLNC mutations (5 truncating and 4 missense). In 3 patients (23%) clinical onset was characterized by major arrhythmic episodes and in one (8%) by sudden death. In 6 (46%) ECG was unremarkable and the most common abnormalities were low QRS voltages in peripheral leads (85%), followed by T wave inversion in lateral (15%) and in inferior leads (16%). Twenty-four-hours ECG monitoring revealed a high arrhythmic burden (PVC >500/die) in 6 cases (46%). CMR was performed in all patients. Four of them (31%) showed a LV dilatation, while in 2 cases (15%) a RV dilatation was present. In 8 (61%) a fatty infiltration was detected mainly affecting the left ventricle (6 cases, 46%). Moreover, late enhancement was present in 8 cases (62%), with a LV distribution. Conclusions: This is the first studied population in which both truncating and missense variants were evaluated as causative of AC, confirming that FLNC gene mutations are rare (4% of probands without known AC causative mutations) and the prevalent clinical expression is a left dominant phenotype with a high degree of electrical instability and recurrence of sudden familial cardiac death. Funding Acknowledgement: Type of funding source: None